2008
DOI: 10.1017/s0266467408004823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat degradation on mixed-species bird flocks in Indian rain forests

Abstract: Abstract:Habitat degradation affects mixed-species bird flocks (flock hereafter) through two mechanisms – changes in the bird community from which flocks are drawn and changes in the propensities of species to flock. We determined the relative influence of these two mechanisms by examining variation in flocks across nine rain-forest fragments (range 11–2600 ha) in a plantation landscape in the Western Ghats, India. We found differences between fragments in average number of species (range 10.8–15.2) and indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 37 publications
4
59
2
Order By: Relevance
“…b Higher average association strength observed across guilds compared with within guild. c Field methods used in this study were the same as those used in the study by Sridhar and Sankar (2008). d Field methods used to collect these unpublished data were the same as those used in the published study by Ewert and Askins (1991).…”
Section: Calculation Of Association Strengthmentioning
confidence: 99%
“…b Higher average association strength observed across guilds compared with within guild. c Field methods used in this study were the same as those used in the study by Sridhar and Sankar (2008). d Field methods used to collect these unpublished data were the same as those used in the published study by Ewert and Askins (1991).…”
Section: Calculation Of Association Strengthmentioning
confidence: 99%
“…To date, research on how mixed-species flocks change along disturbance gradients have largely focused on species richness and encounter rates (e.g. number of detections per unit time [32,33]), yet no studies, to our knowledge, have examined how habitat modifications influence interspecific interactions and the stability of flock structure.…”
Section: Introductionmentioning
confidence: 99%
“…The first is fragmentation (Stouffer and Bierregaard 1995;Fernández-Juricic 2000, 2002Marini 2000, 2004;Tellería et al 2001;Van Houtan et al 2006;Sridhar and Sankar 2008;Cordeiro et al 2014;Mokross et al 2014). The general result of this literature is that flock qualities (size in individuals, species richness, encounter rate and even network characteristics; see Mokross et al 2014 about networks) decrease as fragmentation increases, with fragments below 10 ha being especially effected (Maldonado-Coelho and Marini 2004;Mokross et al 2014).…”
Section: Empirical Studies Of How Flocks Respond To Anthropogenic Dismentioning
confidence: 99%
“…In studying how flocks respond to anthropogenic disturbance, several studies have tried to distinguish between how disturbance affects flocks and how it affects the pool of birds at an area available to flock, by taking into account data on the overall abundance of birds in the community (Fernández-Juricic 2002;Sridhar and Sankar 2008;Sidhu et al 2010;Goodale et al 2014). While Fernández-Juricic (2002) found that the total bird density in fragments was a good predictor of the probability of encountering flocks, the other studies found that flocking propensity decreased in highly modified environments (very small fragments in Sridhar and Sankar 2008; and areas of intense agriculture for the studies of Sidhu et al 2010;Goodale et al 2014).…”
Section: Empirical Studies Of How Flocks Respond To Anthropogenic Dismentioning
confidence: 99%
See 1 more Smart Citation